2013
DOI: 10.2118/153216-pa
|View full text |Cite
|
Sign up to set email alerts
|

Microtomographic Characterization of Dissolution-Induced Local Porosity Changes Including Fines Migration in Carbonate Rock

Abstract: Summary The microstructure of carbonate rocks experiences substantial changes under reactive processes, in particular chemical dissolution and deposition, including dissolution-released-fines migration occurring during acidizing. A better understanding of such changes at the pore scale and their influences on rock properties is of great value for the effective design and implementation of reactive processes in carbonate reservoirs. In this work, we demonstrate the use of X-ray micro-computed tom… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
49
0
2

Year Published

2015
2015
2022
2022

Publication Types

Select...
5
1

Relationship

1
5

Authors

Journals

citations
Cited by 43 publications
(54 citation statements)
references
References 8 publications
3
49
0
2
Order By: Relevance
“…Few recent publications document a typical φ − k relationships with transient negative correlations (Mangane et al 2013;Qajar et al 2013;Luquot et al 2014). Limestones are formed by the aggregation of grains spanning a large range of sizes and degrees of induration and cementation among particles at the submicron level.…”
Section: Introductionmentioning
confidence: 99%
“…Few recent publications document a typical φ − k relationships with transient negative correlations (Mangane et al 2013;Qajar et al 2013;Luquot et al 2014). Limestones are formed by the aggregation of grains spanning a large range of sizes and degrees of induration and cementation among particles at the submicron level.…”
Section: Introductionmentioning
confidence: 99%
“…Details of subresolution pores in voxel-by-voxel analysis of successive images of a sample have been the subject of several studies. Qajar et al (2013) examined dissolution-induced local porosity changes of a carbonate core using 3D microtographic data of pre-and post-alteration sample. They showed that ignoring microporosity leads to inaccurate quantification of the fractions of the medium evolved or unchanged.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
“…Recently, a few studies have addressed quantifying local fines migration and deposition using XMT images. Qajar et al (2013) reported temporal permeability reduction during high-pH reactive flooding of a carbonate core. They showed evidence for particle mobilization from μ-CT images of the pre-and post-dissolution sample and developed a method to quantify the fraction of solid phase locally migrated within the sample.…”
Section: Accepted Manuscriptmentioning
confidence: 99%
See 2 more Smart Citations